DEVELOPMENT OF A WEB-BASED MANAGEMENT INFORMATION SYSTEM FOR ONLINE BOARDING HOUSE RESERVATIONS - Evanka Ahmad Saddam; Yulian Findawati; Suhendro Busono; Armuri Wahyu Azinar (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to develop a web-based boarding house management information system for Kost Titik Kumpul, located in Griyo Mapan Sentosa AB-35, Sedati, Sidoarjo, to address existing issues related to manual data recording, payment verification delays, room availability tracking, and incomplete tenant documentation. Method: The research employs a system development approach using the waterfall model, including problem analysis, system design, implementation, and testing to ensure the system aligns with user needs. Results: The resulting system integrates automated tenant data management, online reservations, real-time room availability monitoring, and digital payment processing, which collectively enhance administrative efficiency, accuracy, and reporting capabilities to local authorities. System testing demonstrates improved processing speed, reduced recording errors, and higher reliability in payment verification compared to the previous manual system. Novelty: The study offers an integrated digital solution tailored to small-scale boarding house operations by combining reservation features, automated administrative workflows, and structured tenant reporting in one platform, representing a modernization approach that has not been widely applied in typical local boarding house businesses.